Should knowledge be shared generously? Tracing insights from past to present and describing a model. Issue 4 (11th July 2016) - Anand, Amitabh; Walsh, Isabelle
Abstract : Purpose: Are people generous at work places? How often do we see people willing to share, when someone seeks knowledge from them without any expectation? What's the point in having knowledge when somebody doesn't share it? Then again, why do firms, reward employees to share their knowledge? ¬ ¬ ? Do sharing knowledge between people needs a commercial acceptance or rewarding inspiration? In firms, people who do not have all the work-related knowledge makes them to seek it from others. Thus, this implies that people can either share their knowledge or hoard knowledge or share partial knowledge. Our research shows that sharing knowledge existed since centuries and was practiced through generosity, with a proven evidence that the more you share the more you get back. We will analyse the role of generosity in sharing knowledge by tracing insights from literature, religion, science and modern day management scholarly views and we show that how it can lead to firm success. In this paper, we will propose a direction for future researchers on how developing generosity towards sharing knowledge. We also propose a model of generosity based on literature and our interpretation. Design/methodology/approach: This paper is based on the extensive reviews from literature, articles, and opinions from scholars. We use a keyword protocol to search the articles from Google scholar and other sources on generosity and knowledge sharing. Findings: This paper finds significant relationships and validated shreds of evidence on how generosity towards knowledge sharing has helped humanity in the past and how generosity can help in firm success. Originality/value: This paper is the first of its kind in trying to explore how developing generosity among people can play role in facilitating knowledge sharing for firm success. This further suggests a new direction of research for scholars engaged in exploring the role of generosity with a proposed model.